Graft type for superior mesenteric and portal vein reconstruction in pancreatic surgery – A systematic review. Issue 4 (April 2021) - Labori, Knut J.; Kleive, Dyre; Khan, Ammar; Farnes, Ingvild; Fosby, Bjarte; Line, Pål-Dag
Abstract: Background: Contemporary practice for superior mesenteric/portal vein (SMV-PV) reconstruction during pancreatectomy with vein resection involves biological (autograft, allograft, xenograft) or synthetic grafts as a conduit or patch. The aim of this study was to systematically review the safety and feasibility of the different grafts used for SMV-PV reconstruction. Methods: A systematic search was performed in PubMed and Embase according to the PRISMA guidelines (January 2000–March 2020). Studies reporting on ≥ 5 patients undergoing reconstruction of the SMV-PV with grafts during pancreatectomy were included. Primary outcome was rate of graft thrombosis. Results: Thirty-four studies with 603 patients were included. Four graft types were identified (autologous vein, autologous parietal peritoneum/falciform ligament, allogeneic cadaveric vein/artery, synthetic grafts). Early and overall graft thrombosis rate was 7.5% and 22.2% for synthetic graft, 5.6% and 11.7% for autologous vein graft, 6.7% and 8.9% for autologous parietal peritoneum/falciform ligament, and 2.5% and 6.2% for allograft. Donor site complications were reported for harvesting of the femoral, saphenous, and external iliac vein. No cases of graft infection were reported for synthetic grafts. Conclusion: In selected patients, autologous, allogenic or synthetic grafts for SMV-PV reconstruction are safe and feasible. Synthetic grafts seems to have a higher incidence of graft thrombosis.